2005
DOI: 10.1086/427925
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium Patterns and tagSNP Transferability among European Populations

Abstract: The pattern of linkage disequilibrium (LD) is critical for association studies, in which disease-causing variants are identified by allelic association with adjacent markers. The aim of this study is to compare the LD patterns in several distinct European populations. We analyzed four genomic regions (in total, 749 kb) containing candidate genes for complex traits. Individuals were genotyped for markers that are evenly distributed at an average spacing of approximately 2-4 kb in eight population-based samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 24 publications
12
84
2
1
Order By: Relevance
“…The same observation was made by Stenzel et al studying LD across the MHC, 35 and even though ethnicity is a parameter influencing LD, maps seem to be transferable among European populations. 36 In contrast to the population similarities, we observed significant variations in LD pattern and haplotype blocks after grouping the data set, according to alleles carried at some HLA loci (i.e. DQB1, DQA1, DRB1, and in some instances MIB).…”
Section: Discussioncontrasting
confidence: 59%
“…The same observation was made by Stenzel et al studying LD across the MHC, 35 and even though ethnicity is a parameter influencing LD, maps seem to be transferable among European populations. 36 In contrast to the population similarities, we observed significant variations in LD pattern and haplotype blocks after grouping the data set, according to alleles carried at some HLA loci (i.e. DQB1, DQA1, DRB1, and in some instances MIB).…”
Section: Discussioncontrasting
confidence: 59%
“…26,27 Moreover, tag-SNPs identified in one population may not be applicable to other populations 28 even if they seem to be quite general for Europeans. 29 Furthermore, Crawford et al, 30 after analyzing the sequence diversity in 100 human genes, concluded that the amount of LD and the haplotype structure should be empirically analyzed in order to assess which and how many SNPs must be typed in a specific gene to detect an association with a disease-causing SNP in a case-control study.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Israeli sample requires more tags than the other populations, after correcting for sample size, indicating that the CEPH sample defined tag set used to define the marker selection did not capture all the variation in the Israeli population. In general, most investigations into LD differences find that Northern Europeans can be grouped together for the purposes of generating and applying tag SNPs [Mueller et al, 2005;Gonzalez-Neira et al, 2006;de Bakker et al, 2006]. Southern Europeans and Israelis tend to form a different population cluster [Bauchet et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…A key component of such work is tag selection from the LD information of the Centre d'Etude du Polymorphisme Humain (CEPH) sample. Mueller et al densely genotyped four gene regions (PLAU, SNCA, LMNA, and FKBP5) at a frequency of one SNP per $2-4 kb in strictly European populations to gauge populations differences [Mueller et al, 2005]. In general, mild allele frequency differences were detected.…”
Section: Introductionmentioning
confidence: 99%